DETERMINATION OF FIRM VALUE IN BASIC INDUSTRY AND CHEMICAL SECTOR COMPANIES ON THE INDONESIA STOCK EXCHANGE - Saputra, Redy; Riyanto Setiawan Suharsono; Rendy Mirwan Aspirandi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to identify, examine, and analyze the factors influencing firm value in basic industry and chemical sector companies listed on the Indonesia Stock Exchange (IDX) in 2023. The research is motivated by the phenomenon of fluctuating firm values in basic industry and chemical sector companies listed on the IDX from 2017 to 2023. Ideally, these companies should attract significant interest due to the everyday relevance of their products. Method: This is a quantitative study employing an explanatory research approach. The independent variables are profitability (Variable 1) and inflation (Variable 2), while the dependent variable is firm value. The research focuses on companies in the basic industry and chemical sectors listed on the IDX in 2023. The data used are secondary data sourced from corporate annual reports. The data analysis methods include descriptive statistical analysis, classical assumption tests, multiple linear regression tests, and hypothesis testing. Results: The results indicate that profitability does not have a significant effect on firm value, inflation does not influence firm value, and profitability and inflation do not simultaneously affect firm value. The conclusion of this study is that all three hypotheses (H1, H2, and H3) are rejected. Novelty: Thus, the findings contribute to and reinforce empirical evidence showing that profitability and inflation do not influence firm value.